A role for cancer stem cells in therapy resistance: Cellular and molecular mechanisms. (April 2015) - Cojoc, Monica; Mäbert, Katrin; Muders, Michael H.; Dubrovska, Anna
Abstract: Similar to normal tissue, many tumors have a hierarchical organization where tumorigenic cancer stem cells (CSCs) differentiate into non-tumorigenic progenies. A host of studies have demonstrated that although CSCs and their non-tumorigenic progenies within the same clone can share common genotype, they display different epigenetic profiles that results in changes of multiple signaling pathways. Many of these pathways confer cell adaptation to the microenvironmental stresses including inflammation, hypoxia, low pH, shortage in nutrients and anti-cancer therapies. Treatment strategies based on combination of conventional therapies targeting bulk tumor cells and CSC-specific pathway inhibition bear a promise to improve cancer cure compared to monotherapies. In this review we describe the mechanisms of CSC-related therapy resistance including drug efflux by ABC transporters, activation of aldehyde dehydrogenase and developmental pathways, enhanced DNA damage response, autophagy and microenvironmental conditions, and discuss possible therapeutic strategies for improving cancer treatment.